2019
DOI: 10.1101/531855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-distance dispersal shaped the diversity of tribe Dorstenieae (Moraceae)

Abstract: 1 Aim: The Neotropics have the highest terrestrial biodiversity on earth. Investigating the 2 relationships between the floras of the Neotropics and other tropical areas is critical to 3 understanding the origin and evolution of this mega-diverse region. Tribe Dorstenieae (Moraceae) 4 has a pantropical distribution and almost equal number of species on both sides of the Atlantic.5In this study, we investigate the relationship between the African and Neotropical floras using 6 Dorstenieae (15 genera, 156 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 68 publications
(125 reference statements)
1
17
0
Order By: Relevance
“…This has led to conflicting views of phylogenetic relationships within the tribe (Berg, 2001; Clement & Weiblen, 2009; Zerega & al., 2010; Gardner & al., in press). A recent phylogenomic study of Dorstenieae, based on a target enrichment approach (Q. Zhang & al., 2019a), confirmed the monophyly of Dorstenieae, which includes Brosimum together with 15 other genera (Zerega & Gardner, 2019; Gardner & al., in press). These include members of the now‐obsolete Brosimeae as well as others ( Bleekrodea Blume, Broussonetia L'Hér.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…This has led to conflicting views of phylogenetic relationships within the tribe (Berg, 2001; Clement & Weiblen, 2009; Zerega & al., 2010; Gardner & al., in press). A recent phylogenomic study of Dorstenieae, based on a target enrichment approach (Q. Zhang & al., 2019a), confirmed the monophyly of Dorstenieae, which includes Brosimum together with 15 other genera (Zerega & Gardner, 2019; Gardner & al., in press). These include members of the now‐obsolete Brosimeae as well as others ( Bleekrodea Blume, Broussonetia L'Hér.…”
Section: Introductionmentioning
confidence: 74%
“…(2016), Q. Zhang & al. (2019a), and the National Center for Biotechnology Information (NCBI) Sequence Read Archive (SRA) to complete the outgroup sampling. All new reads have been deposited in the SRA (BioProject PRJNA322184).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous phylogenetic work including Brosimum includes a two-locus family-level study 124 (with five Brosimum species) based on nuclear ribosomal and chloroplast DNA (Zerega & al.,125 2005; Clement & Weiblen, 2009), a targeted study (12 Brosimum species) based on a single 126 chloroplast locus (Silva, 2007), and a tribe-level study (10 Brosimum species) using a target 127 enrichment approach (Zhang & al., 2019a). They all found that Trymatoccocus and 128…”
Section: Inflorescences 115mentioning
confidence: 99%